HISTORY OF CARDIAC AND THORACIC SURGERY The origins of electrocardiography in Poland - Gryglewski, Ryszard W. (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
The progress of science and technology in the 19th century enabled better understanding of the electrical activity that occurs during a heartbeat. However, it was only the construction and introduction of the galvanometer that cleared the way for appropriate experimental and clinical studies. Marey, Waller, Wenckebach, Einthoven, and Pardee are just examples of the world’s pioneers of electrocardiography. Polish researchers, including Cybulski, Eiger, Rzętkowski, Surzycki, and Latkowski, also contributed to the development of this area of study. The following article is a review aiming to reconstruct the origins of electrocardiography in Poland, both as a measurement method used in experiments and as a diagnostic tool in clinical studies conducted in the years preceding the outbreak of World War I.